E- LEARNING AND E-ASSESSMENT AS THE TEACHING PLATFORM FOR 1ST PROFESSIONAL MBBS STUDENTS IN A TERTIARY MEDICAL COLLEGE OF EASTERN INDIA IN THE COVID ERA - SCOPE AND CHALLENGES - DR RITUPARNA BASU,DR TAPATI ROY (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In the wake of the COVID-19 pandemic, there has been an urgent need in educational institutions around the world, to change their teaching platform so as to ensure continuance of teaching – learning process. Previously, although e-learning platform was known but, presently, e- learning and e – assessment have emerged as the most promising solution. Aim: The present study has been designed to explore the scope and challenges of e- learning and e- assessment from the 1st Professional MBBS students of Eastern India. Settings and Design: Descriptive type of cross sectional study. Methods and Material: 1st Professional MBBS Students Statistical analysis used: Data were collected via Google forms in online mode. Software (SPSS 22.0 trial version) was used for data analysis. Results: Out of 250 students, 232 students responded to the present study. Different tools were used to conduct online classes and assessment namely, Microsoft Team, You Tube, Google classroom. The results were tabulated and analyzed. There were some factors that supported e-learning like time flexibility (58.6%), location flexibility (45.3%) and suitability to take and submit tests (55.4%), while some factors went against e – learning. 62.2% and 48.7% students agreed that the most effective tool was You tube and best form of e-assessment was Google classroom respectively.78% students disagreed that live lectures over internet were as effective as physical lectures and 84.5% students supported that e-learning was not suitable for practical classes. 64.75% students preferred combined classes. Conclusion: We concluded a combination of physical and online platform still serves as the best teaching platform for Medical students